Correlation of disability with anxiety and depression in patients with chronic non-specific neck pain: a cross-sectional observational study - Geete, Dipti B.; Mhatre, Bhavana S.; Iyer, Saraswati (International Journal of Research in Medical Sciences, 2022)
Background: Neck Pain is a prevalent musculoskeletal condition usually associated with disability. Psychological illnesses like anxiety and depression are commonly seen in chronic pain. The purpose of this study was to evaluate the relationship between anxiety, and depression with disability in patients with chronic non-specific neck pain. Methods: 87 patients with chronic non-specific neck pain were recruited in this cross-sectional study. The disability was evaluated with neck disability index, anxiety with the generalized anxiety disorder scale (GAD-7), and depression with patient health questionnaire (PHQ9). Results: Out of 87, 60 were females and 27 were male. For correlation, Spearman’s test was applied for the outcome measures. There was a moderate positive correlation found between disability and anxiety (r=0.55) and between neck pain and depression (r=0.63). Conclusions: There is a moderate positive correlation between self-reported disability and anxiety (GAD7) and also between self-reported disability and depression (PHQ9) in patients with chronic non-specific neck pain.